2017
DOI: 10.1186/s12937-017-0247-4
|View full text |Cite
|
Sign up to set email alerts
|

Dose-response relationship between dietary magnesium intake, serum magnesium concentration and risk of hypertension: a systematic review and meta-analysis of prospective cohort studies

Abstract: BackgroundThe findings of prospective cohort studies are inconsistent regarding the association between dietary magnesium intake and serum magnesium concentration and the risk of hypertension. We aimed to review the evidence from prospective cohort studies and perform a dose-response meta-analysis to investigate the relationship between dietary magnesium intake and serum magnesium concentrations and the risk of hypertension.MethodsWe searched systematically PubMed, EMBASE and the Cochrane Library databases fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
101
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(106 citation statements)
references
References 56 publications
2
101
0
3
Order By: Relevance
“…Anti-hypertensive effects of DASH dietary components are biologically plausible, given the high intake of constituents like phytochemicals and nutrients such as magnesium, potassium, calcium, lactotripeptides, selenium, zinc, antioxidants, vitamins, unsaturated fatty acid, and fibre which have been shown to lower blood pressure (Alonso et al 2006;Appel et al 2006;Fekete, Givens, and Lovegrove 2015;Han et al 2017;Houston 2011;Schwingshackl, Strasser, and Hoffmann 2011;Whelton et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Anti-hypertensive effects of DASH dietary components are biologically plausible, given the high intake of constituents like phytochemicals and nutrients such as magnesium, potassium, calcium, lactotripeptides, selenium, zinc, antioxidants, vitamins, unsaturated fatty acid, and fibre which have been shown to lower blood pressure (Alonso et al 2006;Appel et al 2006;Fekete, Givens, and Lovegrove 2015;Han et al 2017;Houston 2011;Schwingshackl, Strasser, and Hoffmann 2011;Whelton et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…A number of prospective cohort studies have examined the association between circulating Mg levels and incidence of CHD [ 23 27 ], hypertension [ 26 , 28 , 29 ], or T2DM [ 11 , 30 32 ], but the findings are inconsistent and inconclusive. One recent meta-analysis examined both dietary intake of Mg and circulating Mg levels with the risk of CHD found an inverse association [ 33 ]. Earlier, two meta-analyses found that circulating Mg concentrations were inversely related to the risk of CVD [ 13 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Combining all trial results demonstrates a 3-4/2-3 mm Hg systolic/diastolic blood pressure reduction within 3-24 weeks postintervention. 31 Supporting these data, Guerrero-Romero et al observed in a cross-sectional study of otherwise healthy Mexican children (n ¼ 3954) that serum magnesium levels ,1.8 mg/dL were associated with prehypertension and hypertension, defined as blood pressures exceeding the age range-specific 95th percentile. 32 The importance of maintaining magnesium levels in hypertensive patients who are often diabetic should not be forgotten.…”
Section: Magnesium In Hypertensionmentioning
confidence: 83%